The Effect of Contact Type on Perceptions of Sex Offender Recidivism Risk - Walker, Donald (2017)
Prior research has found that the general public perceives sex offenders negatively as a whole (Edwards & Hensley, 2001). These perceptions have enabled sex offender management policies that create ironic conditions for sex offender rehabilitation and reintegration (Hanson, & Harris, 2000). More recent research has found that when sex offenders are presented as subcategories the public has more varied, though still negative attitudes toward sex offenders (King & Roberts, 2015). Furthermore, a burgeoning area of research has developed around the differentiation of child sex offenders based on the contact that they have had with their victims: non-contact, contact-only, and mixed-contact. The present study examined the effect that contact type has on perceptions of recidivism for child sex offenders, and whether the presentation of statistical information would affect these perceptions. There was a significant differentiation of perceptions of recidivism across contact types. Participant sex had a significant effect such that women perceived sex offenders as more likely to recidivate than male participants. Moreover, presenting statistical information to participants significantly reduced their perceptions of recidivism; although these perceptions remained significantly higher than the empirical data for recidivism. These results have significant implications for outreach programs that may seek to better educate the public about sex offenders and the development of sex offender management policies with a more empirically-based approach